Pemberdayaan Masyarakat Melalui Diversifikasi Produk Labu Kuning Pada Kelompok Wanita Tani Sukses Makmur Di Desa Tambang Ulang Kabupaten Tanah Laut - Susi Susi; Lya Agustina; Alia Rahmi (Universitas Lambung Mangkurat, 2021)
The development of small rural agro-industry based on local commodities such as pumpkin (waluh) is important in order to increase the added value of the product. The abundance of pumpkins in Tanah Laut Regency has not been used optimally. The women farmer group of Sukses Makmur in Tambang Ulang Village, Tanah Laut Regency really hopes to have a source of income or entrepreneurship that can be managed by them as a source of family income and to develop a productivity. Iptek Bagi Masyarakat Program (IBM) for the community include the stages of socialization, counseling and training on pumpkin-based products with the facilitation of appropriate and attractive packaging as promotional media efforts. Products are also facilitated to obtain PIRT legality from the Health Office. The implementation of science and technology for the community, it showed that KWT Sukses Makmur are able to play an active role in the activities carried out which include several stages of training on pumpkin-based product diversification. Pumpkin-based products that can be produced include brownies, cakes, sponge cakes, pastels, donuts, puddings, wajik, sticks, and sweet breads. The production of pumpkin chips used a vacuum frying facility from BP3T South Kalimantan has been tested. Marketing activities have been carried out through door to door techniques and exhibition promotions, one of which is at the Expo South Kalimantan exhibition. It needs support from relevant agencies, especially the Tanah Laut Health Office where to get a PIRT to improve product marketing and promotion. This activity is also able to make the production of processed pumpkin a new entrepreneur and create entrepreneurial women who are able to maintain its sustainability. Keywords : pumpkins, diversification, Tambang Ulang, enterphreneurship